The Effect of Health Education (Counseling Method) on DHF Prevention on the Knowledge of the Elderly in the Working Area of PB Selayang II Medan Health Center in 2023 - Junita Florida Hasugian (SEAN Institute, 2023)
Dengue hemorrhagic fever (DHF) is a disease that can be transmitted to humans through the bite of Aedes aegypti or Aedes albopictus mosquitoes. Dengue hemorrhagic fever (DHF) is still one of the most common diseases in PB Selayang II Health Center, Medan Selayang District, Medan City, in addition to upper respiratory tract infections (ARI) (Widiastuti, 2008). The purpose of this study is to determine the effect of health education (counseling method) on dengue prevention on the knowledge of the elderly in the working area of the Pb Selayang II Medan Health Center in 2023. This type of research is a type of Quasi-Experimental research with a Pre-Experimental research design, with the research design used is One Group Pretest-Posttest Design. The population used in this study was all elderly at Puskesmas Pb Selayang II Medan with a sampling technique using a total of 56 people. Based on the results of the study, it shows that providing counseling on dengue prevention on the knowledge of the elderly in the working area of the PB health center in 2023 can increase knowledge by 8.50, from 9.46 during the pre-test to 17.96 during the post-test. The results of the T test obtained a P-Value value of 0.000 (<0,05), so it can be concluded that there is a significant difference in the level of knowledge before and after counseling. These results show that counseling methods can increase the knowledge of the elderly about DHF prevention. The hope is that health counseling activities like this can be carried out in a sustainable manner, in order to increase knowledge and the public about health.